Предмет: Алгебра, автор: timibom03

(8b-8)(8b+8)-8b(8b+8) при b=2,6

Ответы

Автор ответа: angelina01010
0

Ответ:

-230,4

Объяснение:

(8b-8)(8b+8)-8b(8b+8)=64b²-64-64b²-64b=-64b-64=-64×2,6-64=-166,4-64=-230,4

Автор ответа: Аноним
2

Решение:

(8b - 8)(8b + 8) - 8b(8b + 8) = 64 {b}^{2}  - 64 - 64 {b}^{2}  - 64b =  - 64b - 64 =  - 64 \times (b + 1)

при b = 2,6

 - 64 \times (2,6 + 1) =  - 64 \times 3,6 =  - 230,4

Ответ:  - 230,4

Похожие вопросы
Предмет: Литература, автор: Арси115
Предмет: Немецкий язык, автор: lWater